A school-based programme promoting healthy eating. (April 2020) - Chan, Kara; Siu, Judy Yuen-Man; Lee, Albert
Objective: Many school-based health education programmes adopt a one-way, top-down communication approach that students tend to consider boring and ineffective. In contrast, this study tested a pilot school-based health education programme designed to engage students through the creation and production of health-related advertising. Design: Participatory action research. Setting: A secondary school located in the most deprived district in Hong Kong. Method: A 10-month health education programme was implemented which included health talks and a parent–child cooking workshop. The highlight of the programme was a contest to design a healthy eating public service announcement with professional production of the winning advertisement. A convenience sample of 67 secondary school students participated. Self-administered food diaries and focus group interviews were administered before and after the programme for evaluation. Results: Among all the health education activities conducted during the programme, the participating students found the advertisement design contest the most interesting. They appreciated the opportunity to see their creative ideas consolidated in a professional manner. Dietary patterns reported in food diaries did not show any significant change, but the post-programme focus group interviews reported a remarkable increase in healthy eating knowledge. There were some self-reported changes in dietary behaviours. Conclusion: In the digital age, engaging students in content creation is a possible way to interest them in adopting healthy eating behaviours.